(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
We determine in this work the physical parameters of a pulsating star. The star was discovered during our survey on a field of stars in the Pleiades open cluster. The field was observed in the period 2008– 2010 and recently 2020 with the main telescope’s camera of 0.9 m at the University Observatory Jena in Germany. Our new star has an orbital period of about days. The location of this new star in the HRD is inconsistent with the age and distance of the already known Pleiades stars in this field, so that it’s not valid as a Pleiades member candidate. The derived spectral type of this new star is F2V. The derived mass and radius of this new star are , respectively. is the solar mass, and is the solar radius.